KARAKTERISTIK ALTERASI DAN MINERALISASI ENDAPAN EPITERMAL SULFIDASI TINGGI DI DAERAH BAKAN, KABUPATEN BOLAANG MONGONDOW, PROVINSI SULAWESI UTARA: CHARACTERISTICS ALTERATION AND MINERALIZATION OF HIGH SULPHIDATION EPITHERMAL DEPOSITS IN BAKAN AREA, BOLAANG MONGONDOW REGENCY, NORTH SULAWESI PROVINCE - Farrel Gibran Hafizha Khansa; Aton Patonah; Cecep Yandri Sunarie; Devito Pradipta (Buletin Sumber Daya Geologi, 2026)
The Bakan area, Bolaang Mongondow Regency, North Sulawesi Province is one of the regions with gold deposit potential in Indonesia. This study aims to identify the characteristics, alteration, and mineralization in the research area through field observations, petrography, mineralography, analytical spectral devices, fire assay (FA), and Atomic Absorption Spectrophotometry (AAS). Based on the alteration mineral assemblage, the research area is divided into five alteration zones: quartz (vuggy) + alunite, quartz (massive) + alunite, alunite + dickite + kaolinite + quartz, illite + montmorillonite, and chlorite + epidote. The mineralization in the research area consists of oxide and sulfide minerals. Oxide minerals include goethite hematite and jarosite. Sulfide minerals include pyrite, sphalerite, galena, chalcopyrite, and covellite. Integrating all data, the type of hydrothermal deposit in the research area is an epithermal high-sulfide deposit with the precious metal mineralization potential zone located in the central area of the research region. The mineralization zone is associated with the massive silica and vuggy silica alteration zones, which are dominantly controlled by structures oriented Northeast - Southwest.